2021
DOI: 10.4103/jmhhb.jmhhb_127_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Diagnostic Tools Predictability of Common Mental Disorders among Indian Children and Adolescent Population

Abstract: The objective of this systematic review was to examine the pooled prevalence of common mental disorder (CMD) and to evaluate the predictability of screening instruments to detect CMD in the children and adolescent population in India. Data sources included the MEDLINE, PubMed, PyschEXTRA, and PyschINFO up to 2020, with additional studies identified from a search of reference lists to examine the diagnostic utility of tools carried out in accordance with the Preferred Reporting Items for Systematic Review and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Internalizing disorders seem to be as common or higher than externalizing disorders in children and adolescents. Internalizing disorders primarily include depression, anxiety, social withdrawal, and somatic problems (Radhika et al, 2021). Considering their association with subjective distress and functional impairments, there is a need to examine the factors associated with the internalizing disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Internalizing disorders seem to be as common or higher than externalizing disorders in children and adolescents. Internalizing disorders primarily include depression, anxiety, social withdrawal, and somatic problems (Radhika et al, 2021). Considering their association with subjective distress and functional impairments, there is a need to examine the factors associated with the internalizing disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Other classifications have also included dissociative disorders, and trauma and stress related disorders under internalising problems (Regier et al, 2013). A recent meta-analysis showed that the pooled prevalence of internalising disorders such as depression in children and adolescents was 19.3%, anxiety was 15% and other depressive disorders were 11% (Radhika et al, 2021).…”
mentioning
confidence: 99%